The Impact of Parental Behaviors on Children’s Lifestyle, Dietary Habits, Screen Time, Sleep Patterns, Mental Health, and BMI: A Scoping Review - Cátia Maia; Diogo Braz; Helder Miguel Fernandes; Hugo Sarmento; Aristides M. Machado-Rodrigues (Children)
Background and Objectives: Childhood obesity and being overweight are influenced by the family environment, diet, sleep, and mental health, with parents playing a key role in shaping behaviors through routines and practices. Healthy parental habits can encourage positive outcomes, while poor routines and stress often lead to unhealthy weight gain. This study analyzed the impact of parental behaviors on children’s lifestyles and habits, as well as the trend and intensity of the effect of these behaviors on different age groups. Methods: A systematic review of 1504 articles from Web of Science, PubMed, Scopus, and APA PsycNet (as of 22 July 2024) included studies on parents and children aged 4–18 years, focusing on physical activity, sleep, screen time, nutrition, and mental health. Twenty-six studies were analyzed, including 19 cross-sectional and 7 longitudinal studies. The outcomes included physical activity, sedentary behaviors, eating and sleeping habits, mental health, and BMI. Bias was assessed using JBI tools according to the GRADE framework and Newcastle-Ottawa Quality Assessment. Results: The studies involved 89,545 youths and 13,856 parents. The key findings revealed associations between parental physical activity, sleep, dietary habits, mental health, screen time, and their children’s BMIs. Parenting styles significantly influence children’s behaviors. This review highlights the crucial influence of parenting styles and behaviors on children’s physical activity, diet, sleep, and mental health, emphasizing the link between family dynamics and childhood obesity. The findings stress the importance of targeting parental habits in interventions focused on healthy routines and stress management. Longitudinal studies are needed to determine causality, while research involving diverse populations is essential to enhance the applicability of these findings.